The Process of Achieving Inner Peace in the Congregation of the Dhikr Assembly - Ahmad Saifuddin; Nitia Wahid Siti Syamsiyah (Academica: Journal of Multidisciplinary Studies, 2025)
Research examining the psychological condition of congregants during the practice of dhikr and its impact on inner peace remains relatively limited. Objective: This article aims to explain the process through which inner peace is formed among members of the Annisa Dhikr Assembly (Majelis zikir Annisa) in Matesih, Karanganyar, Central Java, Indonesia. Method: This study employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews and participant observation and were analyzed to capture the congregants’ subjective experiences while engaging in dhikr practices. Results: The findings indicate that congregants’ experiences of inner peace are dynamic and shaped by several key dimensions, including physiological, psychological, spiritual, and social support aspects. The interaction among these dimensions contributes significantly to the emergence of feelings of calmness and inner tranquility. In addition, inner peace is influenced by contextual factors such as the presence of the dhikr leader, the leader’s vocal intonation during the dhikr recitation, the style of delivery, and the congregants’ level of understanding of the meaning and practice of dhikr. Conclusion: These findings suggest that dhikr functions not merely as a religious ritual, but also as a psychospiritual experience that plays an important role in fostering inner peace among congregants.